2020
DOI: 10.1111/tbed.13565
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling animal exposure profiles of human Q fever cases in Queensland, Australia, using natural language processing

Abstract: Q fever, caused by the zoonotic bacterium Coxiella burnetii, is a globally distributed emerging infectious disease. Livestock are the most important zoonotic transmission sources, yet infection in people without livestock exposure is common. Identifying potential exposure pathways is necessary to design effective interventions and aid outbreak prevention. We used natural language processing and graphical network methods to provide insights into how Q fever notifications are associated with variation in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
0
10
1
Order By: Relevance
“…While this study demonstrated that C. burnetii exposure was higher in AWRs compared to the general population, and although QFD notification data suggests that macropods are potential sources of infection [ 15 , 16 , 32 ], we were unable to demonstrate a positive correlation between C. burnetii seropositivity and exposure to macropods (adults or juveniles) within this cohort based on the responses to the questionnaire. Nor were we able to identify that exposure to ruminants, other domestic animals or other wildlife, or being present at non-human births were risk factors for C. burnetii seropositivity.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…While this study demonstrated that C. burnetii exposure was higher in AWRs compared to the general population, and although QFD notification data suggests that macropods are potential sources of infection [ 15 , 16 , 32 ], we were unable to demonstrate a positive correlation between C. burnetii seropositivity and exposure to macropods (adults or juveniles) within this cohort based on the responses to the questionnaire. Nor were we able to identify that exposure to ruminants, other domestic animals or other wildlife, or being present at non-human births were risk factors for C. burnetii seropositivity.…”
Section: Discussioncontrasting
confidence: 71%
“…Nor were we able to identify that exposure to ruminants, other domestic animals or other wildlife, or being present at non-human births were risk factors for C. burnetii seropositivity. This was surprising given that the majority of QFD notifications are ruminant associated [ 15 , 16 , 32 ], and that birth products of infected animals, particularly ruminants, can potentially contain high levels of C. burnetii [ 46 , 68 ]. In this study, seropositivity was also not associated with tick bites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruminants, such as cattle, sheep and goats, remain the primary animal reservoir for the bacterium, 3, 6–8 experiencing largely subclinical infections with occasional reproductive impairment, 9, 10 including abortion, dystocia, reduced fertility and neonatal deaths 7, 9 . Indeed, contact with aborted ruminant reproductive materials and the normal products of parturition are considered high risk exposures for Q fever in humans 6, 8, 11–16 …”
Section: Figurementioning
confidence: 99%
“…The distribution of Q fever in Australia is geographically uneven with ‘hotspots’ in central Queensland and around the New South Wales‐Queensland border (>13 cases per 100,000) (Australian Technical Advisory Group on Immunisation (ATAGI), 2018). In addition to livestock, exposures to native wildlife, particularly kangaroos and wallabies, have been associated with human infection, underscoring their role in the epidemiology of Q fever in Australia (Clark et al., 2020; Clutterbuck et al., 2018; Graves & Islam, 2016). A small but notable number of reported human cases did not have animal contact or lacked known risk factors for acquisition (Clutterbuck et al., 2018; Graves & Islam, 2016; Rahaman et al., 2020; Sloan‐Gardner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%